1989
DOI: 10.1016/0014-5793(89)80725-2
|View full text |Cite
|
Sign up to set email alerts
|

Different selectivities of oxidants during oxidation of methionine residues in the α‐1‐proteinase inhibitor

Abstract: myeloperoxidase/H,O,/chloride system and the related compound NH,CI. With taurine monochloramine, another myeloperoxidase-related oxidant, 1.05 mol Met(O) were generated per mol a-l-PI during inactivation. These oxidants attack preferentially one Met residue in a-l-PI, which is identical with Met 358, as concluded from the parallelism of loss of elastase inhibitory activity and oxidation of Met. A similar high specificity for Met oxidation was determined for the xanthine oxidase-derived oxidants. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
(29 reference statements)
5
27
0
Order By: Relevance
“…In this regard, the fact that all free radical scavangers, SOD for superoxide anion, catalase for hydrogen peroxide and mannitol for hydroxyl radicals, significantly inhibited the relaxation of coronary artery strips after EFS in this study conforms with this possibility, since hydroxyl radicals are thought to be generated from superoxide anions by way of hydrogen peroxide in the presence of Fe2+ (Rubanyi & Vanhoutte, 1986 (Hunt et al, 1968;Capeillere-Blandin et al, 1991). It has also been reported that hydroxyl radicals, as well as mydIoperoxide-derived oxidants, induce inactivation of a-l-proteinase inhibitor by oxidation of the reactive site methionine (Met) (Maier et al, 1989). These studies raise the possibility that Met7 and Trp2' in the two important domains of ET-1 recognized by EIA are sites of oxidation by hydroxyl radicals and that the modification of each or both residues leads to the loss of both contractile activity and immunoreactivity of ET-1.…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, the fact that all free radical scavangers, SOD for superoxide anion, catalase for hydrogen peroxide and mannitol for hydroxyl radicals, significantly inhibited the relaxation of coronary artery strips after EFS in this study conforms with this possibility, since hydroxyl radicals are thought to be generated from superoxide anions by way of hydrogen peroxide in the presence of Fe2+ (Rubanyi & Vanhoutte, 1986 (Hunt et al, 1968;Capeillere-Blandin et al, 1991). It has also been reported that hydroxyl radicals, as well as mydIoperoxide-derived oxidants, induce inactivation of a-l-proteinase inhibitor by oxidation of the reactive site methionine (Met) (Maier et al, 1989). These studies raise the possibility that Met7 and Trp2' in the two important domains of ET-1 recognized by EIA are sites of oxidation by hydroxyl radicals and that the modification of each or both residues leads to the loss of both contractile activity and immunoreactivity of ET-1.…”
Section: Discussionsupporting
confidence: 84%
“…These were identified as methionine 358 and another residue thought to be within six residues. Janoff & Carp (17) confirmed that two methionines were oxidized when "1-AT was treated with chloramine-T. Maier and colleagues (45) showed that complete loss of activity of "1-AT occurred when one methionine was oxidized, as determined by amino acid analysis of the total protein. They assumed that this was methionine 358, but their data are consistent with ~50% oxidation of methionines 351 and 358, as shown here.…”
Section: Discussionmentioning
confidence: 95%
“…Other oxidative modifications reported to occur in metal-catalyzed oxidation of proteins in vitro or in vivo include, formation of o-tyrosine from phenylalanine, dityrosine from tyrosine (21,22), and 3,4-dihydroxyphenylalanine (DOPA) from tyrosine (23). Methionine can be oxidized to methionine sulfoxide (24), but it can be reduced back to methionine by peptide-methionine sulfoxide reductase, which is shown to be important in cellular protection against oxidative stress (25,26).…”
Section: Oxidative Modification Of Proteins With Agementioning
confidence: 99%